2017
DOI: 10.1177/2045893217701438
|View full text |Cite
|
Sign up to set email alerts
|

The cancer theory of pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) remains a mysterious killer that, like cancer, is characterized by tremendous complexity. PAH development occurs under sustained and persistent environmental stress, such as inflammation, shear stress, pseudo-hypoxia, and more. After inducing an initial death of the endothelial cells, these environmental stresses contribute with time to the development of hyper-proliferative and apoptotic resistant clone of cells including pulmonary artery smooth muscle cells, fibroblasts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
146
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 155 publications
(198 reference statements)
3
146
0
Order By: Relevance
“…There was also a 4-fold increase in migration and an approximately 25% decrease in apoptosis of MCTPASMCs. These results indicated that the homeostasis of PASMC proliferation, migration and apoptosis was dramatically interrupted in MCT-induced PAH, which coincided to some extent with the features of the quasi-cancerous cells [45][46][47][48][49]. Our data revealed that CaN/NFAT signaling was over-activated in MCT-PASMCs.…”
Section: Discussionmentioning
confidence: 49%
“…There was also a 4-fold increase in migration and an approximately 25% decrease in apoptosis of MCTPASMCs. These results indicated that the homeostasis of PASMC proliferation, migration and apoptosis was dramatically interrupted in MCT-induced PAH, which coincided to some extent with the features of the quasi-cancerous cells [45][46][47][48][49]. Our data revealed that CaN/NFAT signaling was over-activated in MCT-PASMCs.…”
Section: Discussionmentioning
confidence: 49%
“…Interestingly, patients that developed lung cancer exhibited increased IL‐6 levels, and these were lowered following treatment with canakinumab (Ridker et al ., ). These observations parallel the pathobiology of PH which is characterized by marked increases in circulating IL‐6 and is increasingly thought of as a hyper‐proliferative, anti‐apoptotic, metabolically disturbed disorder (Boucherat et al ., ). Notwithstanding, there was a higher incidence of fatal infection and sepsis in those patients receiving canakinumab compared to placebo (Ridker et al ., ).…”
Section: Inflammasomes In Pulmonary Hypertensionmentioning
confidence: 97%
“…It is meaningful and urgent to clarify the pathogenesis of PH. In comparison with previous belief that vasoconstriction acts as a vital role in PH pathogenesis, it is more clearly constituted that pulmonary vascular remodeling is the key 3 causal factor of PH, which is characterized by excessive proliferation and resistance to apoptosis of PASMC and pulmonary artery endothelial cells (PAEC) 2 . PASMC has been proved to play an important role in the development of various types of pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 85%